The psychology of investors’ investment decision-making process: the role of emotion regulation and rumination in investment return - Au, Kah Mun (2023)
Background The inefficiency of the financial market during the outbreak of Covid-19 was highly driven by market sentiment and behavioural bias. Clearly, the irrationality, sentimental and unpredictable financial market movements have repeatedly suggested that there are limitations and impractical applied theories to the existing financial models. Practitioners, regulators, investors, and academicians must be aware that the financial market performances are consequences of investors’ buying and selling decisions, and it is crucial to understand investors’ risk and return of the investment decision-making process to promote financial stability and make necessary adjustments accordingly in improving their financial models. Therefore, this study aims to contribute to the literature on the investors’ decision-making process from a psychological perspective. The objective is to explore the role of investors’ psychological traits, emotions, emotion regulation and affective forecast in the investment decision-making process.